Urethral Duplication with Two Hypospadic Meati-An Unusual Variant - Joseph Rutherford Davidson; Naomi Jane Wright; Massimo Garriboli (Georg Thieme Verlag KG, 2016)
Duplication of the urethra is a rare congenital anomaly, with approximately 300 cases reported in the literature. We report a unique case of this condition in a male infant. This case differs from the classical Effman type II-A2 duplication because of the presence of two hypospadic urethral meati, as opposed to a ventral or dorsal accessory meatus with a normally positioned distal urethra. The patient underwent a single-stage repair consisting of a proximal urethra-urethral anastomosis and distal urethral tubularization at 21 months of age with excellent results in terms of both function and cosmesis.